2013
DOI: 10.1097/mcc.0000000000000033
|View full text |Cite
|
Sign up to set email alerts
|

Whatʼs new in operative trauma surgery in the last 10 years

Abstract: The last 10 years of conflict has produced a wealth of experience and novel techniques in operative trauma surgery. The articles we review here are essential for the contemporary care of the severely injured trauma patient, whether they are card for in a level 1 trauma center or in a field hospital at the edge of a battlefield.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2015
2015
2015
2015

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 48 publications
0
4
0
Order By: Relevance
“…Pelvic bleeding after blunt trauma has traditionally been difficult to control surgically. Although recent reports have documented success with preperitoneal packing of pelvic bleeding, 46,47 angiographic embolization of pelvic bleeding has become a mainstay for definitive control of massive pelvic bleeding [48][49][50] after blunt trauma. This technique of angiographic embolization of pelvic bleeding currently requires fluoroscopy.…”
Section: Damage Control Resuscitationmentioning
confidence: 99%
“…Pelvic bleeding after blunt trauma has traditionally been difficult to control surgically. Although recent reports have documented success with preperitoneal packing of pelvic bleeding, 46,47 angiographic embolization of pelvic bleeding has become a mainstay for definitive control of massive pelvic bleeding [48][49][50] after blunt trauma. This technique of angiographic embolization of pelvic bleeding currently requires fluoroscopy.…”
Section: Damage Control Resuscitationmentioning
confidence: 99%
“…Assessment of national civilian trauma center uptake of innovations regarding the management of severe traumatic brain injury by Piper et al 24 reveal parallel trends in domains of surgical trauma care corresponding to battlefield innovation for the treatment of traumatic brain injuries/mild traumatic brain wounds. 5,14 In their survey of TMD, Piper et al 24 revealed that >80% of responding trauma centers across the United States acknowledge that they do not follow the 2007 guidelines of the Brain Trauma Foundation---developed, at least in part, based on military experience---in >75% of trauma cases. 24 The data presented in this study further show that busier, greater-level trauma centers more readily adopted military practices than smaller centers or centers with less overall trauma volume---a tendency that may reflect larger proportions of military-affiliated providers and staff, increased likelihood of exposure to battlefield innovations via affiliation with an academic institution, and/or greater-volume trauma bays that more closely mimic the conditions and corresponding benefits associated with battlefield innovation.…”
Section: Discussionmentioning
confidence: 97%
“…With it have come a cadre of accompanying battlefield innovations, including advances in trauma resuscitation and hemostasis, [5][6][7][8][9] trauma databases and reporting systems, 5,10,11 tactical combat causality care, 12,13 and treatment of traumatic brain injuries/mild traumatic brain wounds. 5,14 In the 12 years since multinational coalition forces deployed to Iraq (Operation Iraqi Freedom) and the 14 years since Operation Enduring Freedom in Afghanistan began, the establishment of clear definitions, 1,15 measureable outcomes, 1,16 and trauma innovations [5][6][7][8][9][10][11][12][13] have led to dramatic improvements in trauma outcomes among military patients. 1,12,17 Military investment in trauma research through the Defense Health Program and development of the Department of Defense Joint Trauma System and its associated trauma registry have enabled systematic identification and adaptation of both novel and existing operative techniques that, in partnership with civilian trauma researchers, have lead to development of a documented series of ''battlefield innovations.''…”
Section: Expansion Of the Therapeutic Arsenal For Complexmentioning
confidence: 99%
See 1 more Smart Citation